La transizione alla scuola superiore: modello teorico, costruzione e validazione della Scala di Difficoltà di Transizione (SDIT) - Vega Scalera; Fabio Alivernini (LED Edizioni Universitarie, 2010)
High School Transition: Theoretical Underpinnings, Development and Validation of the Transition Difficulty Scale - SDIT The transition into senior high school is a critical juncture in the Italian education system and requires a challenging adaptation for students entering a new learning environment. It could be positive, by providing opportunities for personal growth, or negative when the new school setting is not sensitive to students' needs for autonomy, competence and relatedness. In the transition year, the so-called «transition selection process» has very alarming features. In Italy there are only a few studies in this field compared to other countries, mainly the United States. However, despite its relevant accomplishments, international research on school transitions only seldom address students' transition experience directly by using theoretically based tools with sound psychometric properties. The purpose of this study is to present the conceptual model and the development and validation processes of the Transition Difficulty Scale (SDIT). The study was conducted on a national representative sample of 7.732 students attending the first year of 150 senior high schools. Results of a confirmatory factor analysis attested the mono-dimensional structure of the SDIT and showed factorial invariance across gender and types of schools. The SDIT had satisfactory levels of internal consistency and the correlations among the SDIT scores and the criterion meas ures were consistent with the theoretical framework. In sum, the present findings provide adequate support for construct validity and reliability and for using the SDIT in research and practice, particularly as a screening tool.